Evaluation of aerosol sources at European high altitude background sites with trajectory statistical methods - Salvador, Pedro; Artíñano, Begoña; Pio, Casimiro; Afonso, Joana; Legrand, Michel; Puxbaum, Hans; Hammer, Samuel (Atmospheric environment, 2010)
This study has investigated the influence of synoptic weather patterns and long-range transport episodes on the concentrations of several compounds related to different aerosol sources (EC, OC, SO42−, Ca2+, Na+, K+, 210Pb, levoglucosan and dicarboxylic acids) registered in PM10 or PM2.5 aerosol samples collected at three remote background sites in central Europe. Air mass back-trajectories arriving at these sites have been analysed by statistical methods. Firstly, air mass back-trajectories have been grouped into clusters. Each cluster corresponds to specific meteorological scenarios, which were extracted and discussed. Finally, redistributed concentration fields have been computed to identify the main potential source regions of the different key aerosol components. A marked seasonal pattern is observed in the occurrence of the different clusters, with fast westerly and northerly Atlantic flows during winter and weak circulation flows in summer. Spring and fall were characterised by advection of moderate flows from northeastern and eastern Europe. Significant inter-cluster differences were observed for concentrations of receptor aerosol components, with the highest concentrations of EC, OC, SO42−, K+ and 210Pb associated with local and mesoscale aerosol sources located over central Europe related to enhanced photochemical processes. Emissions produced by fossil fuel and biomass burning processes from the Baltic countries, Byelorussia, western regions of Russia and Kazakhstan in spring and fall also contribute to elevated levels of EC, OC, SO42−, K+ and 210Pb. In the summer period long-range transport episodes of mineral dust from North-African deserts were also frequently detected, which caused elevated concentrations of coarse Ca2+ at sites. The baseline aerosol concentrations in central Europe at the high altitude background sites were registered in winter, with the exception of coarse Na+. While the relatively high concentrations of Na+ can be explained by sea salt advected from the Atlantic, the low levels of other aerosol components are caused by efficient aerosol scavenging associated to advections of Atlantic air masses, as well as lower emissions of these species over the Atlantic compared to those over the European continent and very limited vertical air mass exchange over the continent.